Evaluation of discharge training given by nurses to postpartum mothers to artificial intelligence: an alternative approach to health care - Kerkez, Mujde; Kaplan, Mehmet (BMC, 2025)
ObjectiveThe present study aims to evaluate the discharge training given by nurses to postpartum mothers using artificial intelligence.MethodThe study used a qualitative research design with a descriptive thematic approach and was conducted in a state hospital's maternity ward between April and May 2024. Sixteen nurses with varying experience levels were selected through maximum variation sampling. Data were analyzed using coding and thematic analysis to understand participants' experiences.ResultsAmong the nurses, 81.25% held a bachelor's degree, 43.75% had 6-10 years of experience. Postpartum discharge training emphasized baby cues, sleep management, hygiene, and routine health checks. For maternal care, focus was on rest, vaccinations, avoiding heavy activity, psychological support, exercise, and nutrition. AI provided more comprehensive guidance in both maternal and infant care.ConclusionThis study highlights that AI-assisted guidance is a valuable tool in postpartum discharge training, offering effective general advice. However, human input remains essential for specific and practical recommendations.
Keywords: Artificial intelligence assessment; Discharge education; Nursing education; Postnatal care; Postpartum mothers